2009
DOI: 10.1152/physrev.00040.2008
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Induced Calcium Release in Skeletal Muscle

Abstract: Calcium-induced calcium release (CICR) was first discovered in skeletal muscle. CICR is defined as Ca2+ release by the action of Ca2+ alone without the simultaneous action of other activating processes. CICR is biphasically dependent on Ca2+ concentration; is inhibited by Mg2+, procaine, and tetracaine; and is potentiated by ATP, other adenine compounds, and caffeine. With depolarization of the sarcoplasmic reticulum (SR), a potential change of the SR membrane in which the luminal side becomes more negative, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
232
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(237 citation statements)
references
References 279 publications
3
232
0
2
Order By: Relevance
“…However, in many of these cell preparations, spontaneous cytosolic calcium elevations occur at much higher frequencies, being rather oscillatory than stochastically distributed. Consistently, RyRs and calcium-induced calcium release [37] were shown to be responsible for the occurrence of cytosolic Ca 2+ transients. In microglia, we have shown that spontaneous cytosolic Ca 2+ transients are due to the phasic activity of IP 3 Rs, raising the question for the superordinate signaling that triggers those events.…”
Section: Discussionmentioning
confidence: 64%
“…However, in many of these cell preparations, spontaneous cytosolic calcium elevations occur at much higher frequencies, being rather oscillatory than stochastically distributed. Consistently, RyRs and calcium-induced calcium release [37] were shown to be responsible for the occurrence of cytosolic Ca 2+ transients. In microglia, we have shown that spontaneous cytosolic Ca 2+ transients are due to the phasic activity of IP 3 Rs, raising the question for the superordinate signaling that triggers those events.…”
Section: Discussionmentioning
confidence: 64%
“…The general consensus of these studies is that [Mg 2+ ] at rest is a strong inhibitor of RyR, which keeps the channel closed and unresponsive to the strong activating effect of ATP and Ca 2+ until an action potential activates the cell. Ca 2+ -induced activation of RyR, a key mechanism in cardiac muscle, is apparently not relevant in skeletal muscle (Endo, 2009). At 3 mM [Mg 2+ ], a concentration that can be reached during fatiguing contractions (Westerblad and Allen, 1992), the magnitude of Ca 2+ release achieved by transverse tubule depolarization is reduced (Blazev and Lamb, 1999;Laver et al, 1997;Owen et al, 1996).…”
Section: +mentioning
confidence: 99%
“…Because RYR1 channels are also known to be potentially activated by a rise in cytosolic Ca 2+ (see ref. 8), Ca 2+ -induced Ca 2+ release could be the responsible mechanism. Fig.…”
Section: Resultsmentioning
confidence: 97%